Game “Three Disabled People’s Journey” Through Information Services at Junior High School 6 Palangka Raya - Esty Pan Pangestie; Mimi Suriatie; Oktamia Karuniaty Sangalang; Susi Sukarningsi (Suluh: Jurnal Bimbingan dan Konseling, 2024)
Background: Teachers are important in the activities and efficiency of information services in schools. Teachers can also act as mentors for their students. To help the education process and the quality of human resources, one of the government's policies is to raise guidance and counseling in schools by the Minister's Decree on January 15, 1975 No. 008d / 1975 and 008e / 1975, the following is emphasized again by Decree No. 84/1993 and No. 118/1996, and finally contained in the Merdeka curriculum is interest and talent. Aim: The purpose of this study is" to know the participation of teachers in implementing the use of the game "trip of three disabled people" through information services at Junior High School 6 Palangka Raya ", the sample amounted to 57 teachers at the school.  Method: This research uses a quantitative descriptive method to make planning in a systematic, factual, and accurate manner Regarding the facts, and characteristics of the population so that the results of this research will draw conclusions that only apply specifically to the research object, namely the teachers of Junior High School 6 Palangka Raya.The main data collection tool uses the Check List technique, namely: a way to obtain data by making a list of questions addressed to all teachers at Junior High School 6 Palangka Raya. Result and Discussion: The results of the study showed that almost all components of the objectives in the study were implemented with a fairly high percentage of 100% by teachers in schools. This means that teachers are very involved and support information services at Junior High School 6 Palangka Raya.